Four new species of the Amynthas corticis-group (Oligochaeta: Megascolecidae) from Hainan Island, China - Sun, Jing; Jiang, Ji-Bao; Qiu, Jiang-Ping (Zootaxa, 2012)
This paper describes four new species of earthworms from Hainan Island, China: Amynthas stricosus sp. nov., Amynthas fuscussp. nov., Amynthas montanus sp. nov. and Amynthas genitalis sp. nov. They all belong to the Amynthas corticis-group withfour pairs of spermathecal pores in 5/6–8/9. Amynthas stricosus sp. nov. has postsetal genital papillae within the male poreregion, single or paired in XVII, XIX and XX, a heart-shaped spermathecal ampulla, and the terminal 0.4 of the spermathecaldiverticulum dilated into a band-shaped chamber. Amynthas fuscus sp. nov. has no genital papillae, an irregular heart-shapedspermathecal ampulla, and the terminal 0.25 of the diverticulum dilated into an enlongated ovoid seminal chamber. Amynthasmontanus sp. nov. has two pairs of large ovate and flat-topped genital papillae within the male pore region, diameter0.7–0.8mm, surrounded by epidermal folds, paired on 17/18, 18/19 and accompanied closely with the male pores, heart-shapedspermathecal ampulla, terminal 0.4 of diverticulum dilated into a rod-shaped chamber, with hairpin-looped stalk. Amynthasgenitalis sp. nov. has four longitudinally arranged pairs of ovate and flat-topped genital papillae within the male pore region,diameter 0.4–0.5mm, one paired postsetal and presetal papillae on XVII and XIX respectively, and two paired on XVIIIanterior and posterior to the setal annulet, and small and ovoid spermathecal ampulla, terminal 0.29 of diverticulum dilated into a rod-shaped chamber.